Pengembangan Program Pelatihan Kedisiplinan Kerja (P3K) di Lingkungan Dinas Pendidikan Paluta - Panusunan Panusunan; Emmi Juwita Siregar; Nenni Faridah Lubis; Mutiara Mutiara; Rabiyatul Adawiyah Siregar; Juli Astati Siregar (Jurnal Visi Manajemen, 2024)
This study aims to develop a Work Discipline Training Program (P3K) in the Paluta Education Office environment. The problems studied are 1) How is the level of work discipline of employees in the Paluta Education Office environment? 2) How is the quality of service in the Paluta Education Office? 3) How is the performance of administrative staff in the Paluta Education Office? The research method used is qualitative with a case study approach. Data collection is done through interviews, observation, and document study. The results showed that the level of work discipline of employees in the Paluta Education Office still needs to be improved, especially in the aspect of attendance and compliance with regulations. The quality of service in the Paluta Education Office is also not optimal, with public complaints regarding the slow administrative process. The performance of administrative staff still needs to be improved, especially in communication skills and mastery of information technology. This research resulted in the design of a Work Discipline Training Program (P3K) which is expected to improve discipline, service quality, and employee performance in the Paluta Education Office environment.